2011
DOI: 10.1111/j.1524-4725.2010.01726.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical 5-Aminolevulinic Acid with Intense Pulsed Light versus Intense Pulsed Light for Photodamage in Chinese Patients

Abstract: ALA-IPL PDT has superior rejuvenation effects over IPL alone in Chinese subjects. Taking reasonable precaution to prevent the postinflammatory hyperpigmentation is the most important point in making ALA-IPL PDT a successful therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 23 publications
2
15
0
2
Order By: Relevance
“…With respect of the improvement of sallow complexion and tactile roughness no difference was observed. Similar results were seen in a split‐face study on Chinese patients with a darker skin type [9]. Combined ALA/IPL was significantly superior to sole IPL with respect to the global score for photoaging, fine lines and deep wrinkles.…”
Section: Pdt With Intense Pulsed Light (Ipl)supporting
confidence: 82%
“…With respect of the improvement of sallow complexion and tactile roughness no difference was observed. Similar results were seen in a split‐face study on Chinese patients with a darker skin type [9]. Combined ALA/IPL was significantly superior to sole IPL with respect to the global score for photoaging, fine lines and deep wrinkles.…”
Section: Pdt With Intense Pulsed Light (Ipl)supporting
confidence: 82%
“…Die Evaluation durch die verblindeten Untersucher erbrachte bessere Ergebnisse für den globalen Hautalterungsscore (50 vs. 12,5% p = 0,005), feine Fält-chen (70,8 vs. 33,3% p = 0,009) und grobe Falten (50 vs. 12,5%, p = 0,005) für die Areale nach IPL-ALA-PDT als nach alleiniger IPL-Therapie. Als transiente Nebenwirkungen wurden phototoxische Reaktionen, Ödeme und Erytheme beschrieben [53].…”
Section: Photodynamische Therapieunclassified
“…Studies have shown reduction in lentigines and improvement in overall appearance, skin texture, fine wrinkles and teleangiectasias. [11][12][13] Results after serial treatment with IPL alone are moderate, but combining IPL with photosensitizers such as 5aminolaevulinic acid (ALA) or its methyl ester methyl aminolaevulinate (MAL) 14,15 yield synergistic effects. PDT with IPL is effective in simultaneously treating AK and photoaged skin, [16][17][18][19] and split-face studies have yielded significantly better results for IPL and photosensitizers than for treatment with IPL alone.…”
mentioning
confidence: 99%
“…PDT with IPL is effective in simultaneously treating AK and photoaged skin, [16][17][18][19] and split-face studies have yielded significantly better results for IPL and photosensitizers than for treatment with IPL alone. 15,20,21 The skin of the dorsal hands is susceptible to the first signs of ageing and ages even faster than facial skin. Here, the skin is thinner than in the face, and the density of skin appendages such as pilosebaceous units is also lower.…”
mentioning
confidence: 99%